1985
DOI: 10.3354/meps027001
|View full text |Cite
|
Sign up to set email alerts
|

Diel periodicity of spawning in sciaenids

Abstract: Time of day was determined for spawning of several species of sciaenid fishes by examin~ng development stages of eggs collected in estuarine and near-shore plankton samples. Estuarine samples were taken at different times of day and night but newly spawned Cynoscion nebulosus and Bairdiella chrysoura eggs were taken only during a period from just before to 3 or 4 hours after sunset. Sclaenops ocellatus and Mentichirrhus sp. eggs from near-shore Gulf of Mexico samples, taken during the morning, all contained ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 7 publications
4
84
0
1
Order By: Relevance
“…Moreover, in a related study on Freeport Rocks, Geary et al (in review) reported that hatch dates of red snapper peaked during the new moon. A peak in spawning or hatch during the new moon phase is likely an anti-predator tactic to reduce the success of visual predators that may feed on eggs (Holt et al, 1985), and spawning adults (Nikolsky, 1963). Clearly, dates proximal to the new moon (i.e., first quarter) are also likely to enhance survivorship, since reduced light levels have been shown to reduce the effectiveness of visual predators (James and Heck, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a related study on Freeport Rocks, Geary et al (in review) reported that hatch dates of red snapper peaked during the new moon. A peak in spawning or hatch during the new moon phase is likely an anti-predator tactic to reduce the success of visual predators that may feed on eggs (Holt et al, 1985), and spawning adults (Nikolsky, 1963). Clearly, dates proximal to the new moon (i.e., first quarter) are also likely to enhance survivorship, since reduced light levels have been shown to reduce the effectiveness of visual predators (James and Heck, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Guest and Lasswell (1978) demonstrated in laboratory studies that nocturnal sound production by spawning red drum was associated with males courting females. Holt et al (1985) determined that red drum and other sciaenids are nocturnal spawners, based on egg collections off the coast of Texas. Using a passive acoustic towed hydrophone array, Holt (2008, this issue) located red drum sound production sites in Texas coastal regions (but not in estuaries).…”
Section: Discussionmentioning
confidence: 99%
“…One approach involves mapping the distribution of eggs, larvae, or pelagic juvenile fishes. The spawning areas and times are estimated from age-specific growth data and current patterns, which are projected backwards in time using estimates of fish age, growth, and estuarine hydrography (Holt et al 1985;Peters and McMichael 1987;Johnson and Funicelli 1991). This method is inefficient because of the great amount of work involved in conducting net surveys, the uncertainty over the identity of species collected at early life stages (Daniel and Graves 1994), the extensive knowledge of estuarine hydrography required, and the spatial extrapolation involved.…”
mentioning
confidence: 99%
“…Similar to other studies, black drum and red drum peak calling occurred in the late afternoon and spotted seatrout and silver perch a few hours after sunset (Tavolga 1958, Mok & Gilmore 1983, Gilmore 2003, Locascio & Mann 2008, Lowerre-Barbieri et al 2008, Luczkovich et al 2008, Maruska & Mensinger 2009). Sciaenids most likely spawn at dusk to limit the predation on eggs by many juvenile and adult fishes (Holt et al 1985). Interestingly, spatial and seasonal overlap of calling occurred for silver perch and spotted seatrout in the spring, and for red drum and spotted seatrout in the fall, yet the maximum daily peak in calling was different for each species.…”
Section: Patterns Of Sound Productionmentioning
confidence: 99%
“…In addition, plankton sampling and quantification of eggs and larvae (i.e. by hatching or molecular techniques) does not provide exact information about when and where spawning occurred, since the number of eggs/larvae collected in the field is likely affected by predator activity and water currents (Holt et al 1985, Brown et al 2005, Goffredi et al 2006, Mortensen et al 2015. To our advantage and as discussed previously, many fish produce acoustic signals as part of their courtship behavior.…”
Section: Design By Tim Devine Uscb Graphics Managermentioning
confidence: 99%